A Systematic Literature Review : Content and Pedagogy That Developed in Chemistry Teaching and Learning Materials at Secondary School - Triana Krisandini; Sjaeful Anwar (South Sulawesi Education Development (SSED), 2024)
To improve the efficacy of chemistry teaching and learning in secondary schools, the development of relevant and contextual teacing material is essential. The development of teaching and learning materials is one of the considerable research carried out, especially in the development of chemistry teaching and learning materials for secondary school which is conducted to support an improvement in learning process. This study aims to analyzed contexts of content and pedagogy in the development of chemistry teaching and learning materials. The research method used was a systematic literature review. Employing a systematic literature review method, this study analyzed 51 articles selected from 2015 to 2021 based on keyword “development of chemistry teaching and learning materials in secondary school”. The findings show that context of content and pedagogy that had been used in developing chemistry teaching and learning materials is varied. However, there are certain content in chemistry that oft to developed such as acid-base, chemical equilibrium and colloid, meanwhile context of pedagogy that oft to used in developing chemistry teaching and learning materials are Information and Communication Technology (ICT) and Problem based learning (PBL). Under this literature reviev results, The researcher recommend the continuity the development on chemistry teaching and learning materials not only in content acid-base or chemical equilibrium but also in others that integrated the development to pedagody approches supporting 21st century skills (Critical Thinking, Communication, Collaboration and Creativity).